PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, CAPITAL INTENSITY DAN CORPORATE RISKTERHADAP TAX AVOIDANCE (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Basuki Basuki (JMB : Jurnal Manajemen dan Bisnis, 2018)
Things that need to be done in order to prove independentcommissioners, audit committee, capital intensity and corporate risk ontax avoidance in companies engaged in Indonesia Stock Exchange(IDX). In this study, tax avoidance uses the Cash Effective Tax Rate(CETR) proxy. The research period is 4 years, ie during 2013-2016. Thestudy population covers all manufacturing companies of the industrialsector of goods in the period 2013-2016ALAH 148 companies. Thesampling technique used purposive sampling technique. Based on thecriteria set in the sample of 84 corporate data. Types of data which aresecondary data obtained from the Indonesia Stock Exchange website.The process of data analysis that is panel analysis of regression data.The results showed that independent commissioners and capital intensitydid not have a significant effect, while audit committee and corporaterisk had a significant effect on tax evasion.